Dokumentasi Sejarah Makam Leluhur sebagai Upaya Pelestarian Warisan Budaya Lokal di Desa Jatirejoyoso - Wigati, Aisya Sari Adinda; Damayanti, Yenie Eva (Pakis Journal Institute, 2025)
This community service activity was carried out in Jatirejoyoso Village, Kepanjen District, which is rich in historical and cultural values, reflected through the existence of five ancestral tombs located in each hamlet. Religious and cultural traditions such as pilgrimage (ziarah), nyadran, regular pengajian on Friday Legi nights, and tirakatan nights are still preserved as expressions of respect for the ancestors. However, the lack of documentation has caused the local history to survive only through oral narratives, which risk disappearing over time. This activity aims to record, organize, and preserve the village’s historical narratives using a descriptive qualitative approach. Data were collected through field observations, interviews with community leaders, and visual documentation of the ancestral tomb sites and related cultural traditions. The main outcomes include a documentary video and a historical pocketbook that serve as digital archives and learning media for the community and students. This initiative not only raises awareness of the importance of preserving cultural heritage but also encourages youth participation in strengthening local identity. The documentation serves as an initial step toward maintaining the continuity of local historical heritage amid the dynamics of modern change.